Improvements of soil quality and cocoa productivity with agricultural waste biochar. Issue 1 (January 2022) - Ferry, Y; Herman, M; Tarigan, E B; Pranowo, D
Abstract: National cocoa production has been decreasing, which was in 2017 down to 600, 000 tons/year, only a third quarter of national need. The decline is due to a decrease in national cocoa production caused by lower productivity in smallholder cocoa. In 2003, the productivity was 1, 100 kg/ha/year and in 2017 was only 820 kg/ha/year. The low productivity is caused by pod rot disease, pod borer, and vascular streak dieback (VSD). Not only that, soil degradation was also found to be a contributing factor. Compost or manure have been used as ameliorants, but they should be in high volume and have a short-term effect (3-4 months), easily decomposed, and produce CO2 that damages the ozone layers. A more suitable solution is using biochar which is more resistant to decomposition (hundreds of years), can hold CO2, water, and nutrients from being washed away by erosion. In addition, biochar does not require Cocoa farming generate organic waste that can be processed into biochar, such as cocoa pods, cocoa or shade trees from pruning. The biomass produced can reach up to 8-18 tons/year and is adequate to improve the soil fertility in cocoa plantations.